Psychological resilience and its relationship to the meaning of life of university students (Journal of the College of Basic Education, 2022)
The current search aims is to measure the two variables (Psychological resilience, the meaning of life) among university students And the balance in the two variables (Psychological resilience , the meaning of life) According to gender variable (male, female) And specialization (scientific, humane) among university students As well as to identify the nature of the correlation between (psychological resilience, and the meaning of life) To achieve the objectives of the research two tools were adopted First to measure psychological resilience, and second to measure the meaning of life among university students, They have psychometric characteristics , These tools were applied to a sample of 100 students In a random way from the students of the university and from scientific and humanitarian disciplines, After processing the data statistically The students seemed to Psychological resilience , meaning of life There were also statistically significant differences according to gender variable (male, female) In both: (psychological resilience, the meaning of life) , No significant differences were found In both: (psychological resilience, the meaning of life) According to the variable of specialization (scientific, human), There is also a positive correlation between psychological resilience and the meaning of life, The researcher made a number of recommendations and Suggestions